Proceedings of the 2018 26th ACM Joint Meeting on European Software Engineering Conference and Symposium on the Foundations of 2018
DOI: 10.1145/3236024.3264838
|View full text |Cite
|
Sign up to set email alerts
|

Software fairness

Abstract: A goal of software engineering research is advancing software quality and the success of the software engineering process. However, while recent studies have demonstrated a new kind of defect in software related to its ability to operate in fair and unbiased manner, software engineering has not yet wholeheartedly tackled these new kinds of defects, thus leaving software vulnerable. This paper outlines a vision for how software engineering research can help reduce fairness defects and represents a call to actio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(42 citation statements)
references
References 64 publications
0
42
0
Order By: Relevance
“…Evaluating Models' Bias/Fairness. Evaluating the bias and fairness of a system is important both from a theoretical and a practical perspective [7,41,88,89]. Related studies first define a fairness criteria and then try to optimize the original objective while satisfying the fairness criteria [3,12,13,21,36,46].…”
Section: Related Workmentioning
confidence: 99%
“…Evaluating Models' Bias/Fairness. Evaluating the bias and fairness of a system is important both from a theoretical and a practical perspective [7,41,88,89]. Related studies first define a fairness criteria and then try to optimize the original objective while satisfying the fairness criteria [3,12,13,21,36,46].…”
Section: Related Workmentioning
confidence: 99%
“…In addition, Brun et al insists on the important point in the information system development in consideration of fairness as follows. "(1) eliciting and specifying requirements that capture fairness properties, (2) architecting and designing systems while adhering to their fairness concerns, (3) validating and verifying fairness properties of the resulting software products, and (4) maintaining the fairness properties as the software evolves" [5].Our proposed method contributes to these solutions.…”
Section: B Fairnessmentioning
confidence: 99%
“…However, a small number of opinions may be ignored, as in many cases they will generally make a good choice. In recent years, fairness has become important in the world [5], and it is better to be able to select goals in consideration of this concept.…”
Section: Introductionmentioning
confidence: 99%
“…o f so ftw are en g in ee rin g fo r m ach in e learn in g [2], [3], such as te s t g en eratio n fo r d etectin g fairn ess v io latio n s [5 ]- [7 ], data has greater fairness. Indeed, we found that in 28% of the cases, a larger set of training data even has greater unfairness than a smaller set.…”
mentioning
confidence: 99%